Boronate ester post-functionalization of PPEs: versatile building blocks for poly(2, 2′-(1-(4-(1, 2-di(thiophen-2-yl)vinyl)phenyl)-2-(2, 5-dioctylphenyl)ethene-1, 2-diyl)dithiophene) and application in field effect transistors. Issue 39 (18th September 2015) - Yang, Junwei; Chen, Moyun; Ma, Ji; Huang, Wei; Zhu, Haoyun; Huang, Yuli; Wang, Weizhi
Abstract : Novel boronate esters synthesized by the post-functionalization of PPEs and oligomers can provide an versatile platform for analogues. Abstract : A convenient and scalable strategy for post-functionalization of poly(phenylene-ethynylene)s and phenylene-ethynylene arrays from boronate ester derivatives using the thienyl group as an example. Furthermore, poly(2, 2′-(1-(4-(1, 2-di(thiophen-2-yl)vinyl)phenyl)-2-(2, 5-dioctylphenyl)ethene-1, 2-diyl)dithiophene) showed good field-effect transistor performance with an excellent mobility up to 0.723 cm 2 V −1 s −1 and an on–off ratio of 10 4 .